Effect of hydroponic barley supplementation on production and physicochemical composition of milk from Normande cows - Bir, Abdenour; Meredef, Aissa; Benidir, Mohamed; Eddine Moufok, Charef (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
This study explores the potential of hydroponic barley as an innovative feed strategy to address shortages in intensive livestock production, with a focus on small-scale landless farms. Twelve three-parous Normande cows, averaging 717 ± 34 kg, were allocated into two homogeneous groups based on body weight, calving date, and previous lactation performance. Both groups received identical total mixed rations (TMR), while the experimental group was supplemented with 10 kg of hydroponic barley per cow per day. Over the lactation period, cows in the experimental group exhibited higher daily dry matter intake (20.62 ± 1.21 vs. 19.13 ± 1.14 kg.d-1) and milk production (22.17 vs. 18.91 kg.d-1), resulting in a 17.25 % increase in total lactation yield (6,760.80 vs. 5,765.68 kg). Feed efficiency improved by 9.09 %, and milk composition analysis revealed elevated fat (40.13–42.49 g.kg-1) and protein (32.21–34.87 g.kg-1) concentrations. Daily fat and protein yields were also significantly higher in the experimental group (942 and 758.06 g.d-1, respectively) compared to the control (777.76 and 609.09 g.d-1). No significant differences were observed in body weight or body condition score between groups. These results suggest that hydroponic barley supplementation can enhance both milk yield and quality by improving nutrient intake and digestibility. However, to fully understand the mechanisms underlying these benefits, further investigations are needed to assess its effects on rumen metabolism and gut microbiota. Overall, this study highlighted the practical potential of hydroponic barley as a sustainable, high-value feed supplement in modern dairy systems.